'Finally, I could breathe': the utility and impact of a diagnosis of obsessive compulsive disorder. Issue 3 (12th May 2023) - Hughes, Finn; Kinderman, Peter
Abstract: Background: The diagnosis of obsessive compulsive disorder (OCD) is characterised by intrusive thoughts leading to compulsions to alleviate anxiety. However, research is lacking on impact post-diagnosis. Some research suggests diagnosis may benefit treatment access, but potentially leads to higher levels of stigma and altered self-identity. Aims: The present study assessed the utility (treatment access and problem identification) and impact (stigma, personal wellbeing or social identity) of receiving a diagnosis of OCD. Method: Semi-structured interviews with 12 individuals who had received a diagnosis of OCD were conducted between February and April 2020, then transcribed and analysed using theoretical thematic analysis. Results: Participants reported positive impacts of diagnosis on both 'utility' and 'impact'. Conclusions: The diagnosis of OCD was helpful for participants in making their symptoms tangible, providing relief and hope for recovery. Non-diagnostic or alternative frameworks should aim to meet this need. Future research may wish to identify how this understanding of disorders vary between different diagnoses, especially in terms of stigma and personal wellbeing.